Duck skates - Berry, Lynne; Nakata, Hiroe (New York : Henry Holt and Co., 2005)
Five little ducks skate, romp, and play in the snow.
13 19 31 34
Keywords: Ducks -- Fiction; Snow -- Fiction; Stories in rhyme